The effect of sustained natural apophyseal glides on headache, duration and cervical function in women with cervicogenic headache - Shin, Eui-Ju (Korean Society of Exercise Rehabilitation, 2014)
The objective of this study is to investigate the effect of sustained natural apophyseal glides (SNAGs) on pain and headache duration in women with cervicogenic headache. The method of this study is a single blind and randomized controlled trial. Forty patients with headache were divided randomly into the SNAGs group (n= 20), and control group (n= 20). The expectation of this study was that the SNAGs group, with facilitatory glide, has full range of movement without pain. Sustained end range holds or overpressure can be applied to the physiological movement and subjects in the control group received just light contact to the occipital area for the same amount of time as the SNAGs group, which is three times per week for a period of four weeks. Visual Analogue Scale (VAS), Headache Duration and Neck Disability Index (NDI) were evaluated by patients before and after the intervention. NDI in the SNAGs group showed significantly greater improvement, compared to the control group, in which only the SNAGS placebo technique was applied. In addition, a significantly greater improvement on the visual analogue scale was also observed in the SNAGs group compared with the control group (P< 0.05). In conclusion, the SNAGs technique can help middle aged female patients suffering from cervicogenic headache for relief of cervical pain and headache. It can also be used in physiotherapy on headache.